Jačanje kapaciteta porodica kroz program WHO Caregiver Skills Training (CST): iskustva iz Srbije - Ilić, Snežana; Stojanović, Aleksandra (Specijalna edukacija i rehabilitacija, 2026)
Introduction. The WHO Caregiver Skills Training (CST) program, developed in collaboration between the WHO and the Autism Speaks organization, is based on the principles of positive parenting, developmental-behavioral strategies, and learning in natural contexts. International studies from India, Ethiopia, Hong Kong, and other countries confirm its effectiveness in improving communication, social interaction, and adaptive behavior of children, as well as in strengthening parental competence and well-being. Aim. The aim of this study was to examine the perceived effects of the WHO Caregiver Skills Training (CST) program in Serbia from the perspective of parents who participated in group workshops and home visits during the national pilot implementation. Method. The sample included 32 parents of children aged 2 to 7 years with developmental delays and autism spectrum disorders. Data were collected through an online questionnaire comprising three domains: caregiver skills and behaviors, child development and behavior, and caregiver well-being, complemented by qualitative comments gathered during evaluation interviews. Results. Findings indicate that parents highly value the usefulness of the program, particularly its applicability to everyday routines, improved communication with their children, and increased confidence in the caregiving role. Most parents (87%) reported enhanced child interaction and reduced challenging behaviors, while 75% observed improvements in daily family routines. A notable reduction in feelings of helplessness and isolation was also reported. Conclusion. The results align with international studies and confirm the effectiveness of CST in enhancing early development and strengthening caregiver competence. The study concludes that CST is culturally adaptable and sustainable in the Serbian context, with the potential to become an integral part of the national early intervention system.